Retrospective Analysis of the Efficacy of 10,600nm Carbon Dioxide Laser Ablation for Small Congenital Melanocytic Nevi in Adults - Sakhiya, Jagdish (J Clin Aesthet Dermatol, 2019)
Carbon dioxide (CO(2)) laser ablation treatment generating 10,600nm of infrared radiation has shown promising results in patients with small-sized congenital melanocytic nevi (CMN). In this retrospective study, we evaluated the efficacy (Investigator’s Global Assessment [IGA] score) and patient satisfaction for CO(2) laser ablation for the treatment of small CMN in 17 adults. Of those treated with CO(2) laser ablation, our findings indicate the average IGA and patient satisfaction scores were 6.41 and 3.76, respectively. Apart from these, 47.1 percent of cases obtained an IGA score of 7 and 76.5 percent of cases achieved a patient satisfaction score of 4. These results support the efficacy of CO(2) laser ablation treatment and might help the clinician to guide treatment selection in patients who wish to avoid more invasive surgical options.